Kingdom of Lesotho : Technical Assistance Report-Government Finance Statistics Mission (January 14-25, 2019). (IMF Staff Country Reports; Country Report, 2019)
This paper on government finance statistics (GFS) mission in Lesotho presents a review of progress against recommendations of previous GFS technical assistance (TA) missions and further assist with improving the quality of GFS currently compiled and disseminated. The mission reviewed progress with implementation of previous GFS TA recommendations and updated the public sector institutional table. The mission reviewed the new compilation methods and noted some improvements with the approach. Accounts payable are now recorded under financing, to bridge the timing difference of commitment basis expenditure. The report explains that the legal and institutional environment is conducive to compiling macroeconomic and financial statistics; the relevance and practical utility of existing macroeconomic and financial statistics are monitored; management processes are in place to monitor the quality of macroeconomic and financial statistics; and institutional integrity, transparency, and ethical practices meet statistical standards. There is still a need to correct recording to distinguish expense from acquisition of financial assets.